WORD WALLS FOR INCREASING READING COMPREHENSION SKILL OF PRIMARY SCHOOL STUDENTS: (Classroom Action Research in 3rd grade at Nagreg 04 Elementary School Indonesia University of Education, Nagreg - Bandung) (International Conference on Elementary Education, 2018)
The low results students in reading comprehension caused in the learning activities teacher do not use appropriate media that can support students understanding. English learning always consider as a hard subject by students and students are not interested to read any English textbook because in majority students are lack of English vocabularies, so they get difficulties to understanding in learning English. In this research, the researchers use word walls media of reading comprehension learning. The purposes of this research are to get the image about (1) reading comprehension learning process in fourth grade of elementary school through word walls media and (2) the results of reading comprehension learning in fourth grade of elementary school through word walls media. The research method use in this research is Classroom Action Research (CAR) which developed by John Elliot and design in three cycles. The subject of this research the fourth grade of Nagrog Elementary School. The collection of data obtained through observation, interviews, field notes, tests and documentation. Data obtained from the implementation of research activities and then presented descriptive statistics. Based on the data obtained, it showed an increase of the reading comprehension skill through the use of word walls media. The students averages value in cycle I 55,30; 60,88 in cycle II and the averages value in cycle III 83,28. It can be concluded that reading comprehension learning in elementary school using word walls media can improve student learning results. Therefore, the researchers suggest that word walls as one an effective media to increase learning process and learning results of students in reading comprehension.